FIRM VALUE BASED ON ENVIRONMENTAL ACCOUNTING DISCLOSURE AND INSTITUTIONAL OWNERSHIP - Zulkarnaen, Have (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to analyze the effect of environmental accounting disclosure and institutional ownership on firm value. The population in this study are companies in the basic materials sector (raw goods) listed on the Indonesia Stock Exchange (IDX) in 2020-2023. The sampling technique in this study uses purposive sampling technique. The data obtained in this study comes from secondary data on idx.com. The data analysis techniques used are descriptive analysis, classical assumption testing, hypothesis testing, multiple linear regression analysis with the SPSS version 23 application. The results of the study indicate that environmental accounting disclosure has an effect on firm value. Meanwhile, institutional ownership does not affect firm value because low institutional ownership means that information disclosure tends to be closed and confidential. This causes companies to lose trust and not get recognition from the public due to the lack of information about the company's performance activities.